Rancang Bangun Aplikasi Peramalan Pemenuhan Permintaan Barang pada PT. PEHAESTEX - Wildan, Wildan; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2015)
PT. PEHAESTEX are supplying a variety of products Moslem. Competition in this area is increasing every year and make the sales volume is not stable at PT. PEHAESTEX, especially in products gloves. Problems that occur during this inventory every kind of goods are too little compared to the customer demand that can not meet the demand of customers pelanggan.akibatnya be waiting and customers can switch to another distributor. However, the other type of gloves are also frequent excess stock that made goods become piled up and need a place of their own warehouse for storage. , In the procurement of goods, manager of PT. PEHAESTEX only see the data based on the previous month's demand for goods only. The aim of this thesis was to produce a determination of inventory by forecasting applications meeting the demand of goods with exponential smoothing method winter in PT. PEHAESTEX to help make decisions for supplies after knowing the approximate demand for goods in the future.